Modelling Tax-Consumption Relationship : An Empirical Evidence from Asia - Tan, Shu Hui; Muhammad Asraf, Bin Abdullah (Unimas Publisher, 2019)
This study examines the impact of taxation on consumption behaviour by focusing on selected countries from Asia. The study adopts panel fixed effect and random estimators to gauge the influence of tax on consumption expenditures.Findings of the study support negative influence of tax on household consumption. The finding is parallel with the absolute income hypothesis that high volume of tax collected from the public results in falling households’ disposable incomes, hence downwardly affecting households’ consumption levels. The study’s finding implies the importance of carefully observing an appropriate tax policy that suit the country’s level of development in order to promote high rates of economic growth and consumption.